Classroom to Communities of Practice: Benefits for English Learners and Teacher Candidates Through Partnerships. (2nd January 2018) - Regalla, Michele; Davies, Alex; Grissom, Donita; Losavio, Antonio
Abstract : This study investigates a service-learning program for university students seeking teacher certification examined through the lens of sociocultural theory. Data was collected from teacher candidates (TCs) in the form of surveys and an open-ended writing assignment. Administrators from the partner schools were also interviewed to provide their perspectives of the service learning. Findings show that the service-learning program allowed TCs and their English learners (ELs) to form communities of practice that were mutually beneficial. Teacher candidates reported numerous opportunities to apply the strategies learned in their methods course, as well as an increase in their sense of preparation for teaching ELs. Administrators provided positive feedback about the service-learning program in terms of the relationship between the partner school and the university. Difficulties arose in terms of TCs' accountability and the level of participation afforded to the TCs by the classroom teacher. Implications highlight the importance of negotiating expectations that address the needs of both parties equally in order to support a strong community of practice that prepares TCs to meet the needs of ELs.